Econometric Evaluation of Risk at the Shanghai Stock Exchange - Osińska, Magdalena; Fałdziński, Marcin; Zdanowicz, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The problem of risk transferring is well known in empirical finance. Agents often try to transmit their risk from one market to another when the limit values of their potential losses are being approached or exceeded. When financial markets are completely segmented, risk cannot be transmitted across markets, but on the other hand when markets are integrated and suffer from the same shock, then risk is expected to transmit across markets. Chinese financial market was segmented during Asian crisis 1997–1998 (Lardy (1998)), but during last financial crisis was more vulnerable to risk spillover. The aim of the paper is to analyze the segmentation of the Chinese financial market. We took into account the process of transferring risk between major indices of Shanghai Stock Exchange and sector indices (sub-indices) representing various segments of the market. To check proposed hypotheses we applied Granger causality in risk concept. We applied different risk measures to take into consideration different risk patterns (small, medium and high risk generated locally and/or globally).